Obtenção e caracterização de IPMC´S tendo como material eletroativo nanocompósitos de copolímeros tribloco estireno-butadieno-estireno/nanocristais de celulose - Gall, Paulo Oliveira (2024)
Ionomeric Polymer-Metal Composites (IPMC) are versatile materials with applications in various fields, including robotics, medicine, actuator and sensor technology. These composites consist of a layer of ionomeric electroactive polymer sandwiched between two metallic electrodes. When subjected to an electrical stimulus, they deform in response to the applied voltage, and conversely, they can produce an electrical response when mechanically deformed. Nafion, a sulfonated polymer with a perfluorinated chain, is a commonly used material in IPMC studies due to its excellent ionic conduction properties. However, Nafion has drawbacks such as high cost, poor recyclability, biodegradability issues, and reduced conductivity in low-humidity or high-temperature conditions. To address these limitations, researchers have explored sulfonating other polymers to achieve desirable conductive properties and modify the interaction between constituent monomers, creating nanostructures to enhance conduction. The usage of block polymers like styrene-butadiene-styrene (SBS) makes it possible to control the morphology of the composite and adds versatility to the material. Another area of interest involves incorporating renewable fillers to modify both mechanical properties and ionic conduction mechanisms. Cellulose nanocrystals, with their high hydrophilic character, can improve ionic conduction and mechanical properties while contributing to the sustainability of the material. This approach aligns with the goal of creating sensors based on renewable resources. In the context of this project, sulfonation of the styrenic phase of an SBS-type copolymer, incorporation and dispersion of cellulose nanocrystals, and usage of the resulting composite to manufacture IPMCs is proposed, as well as the impact of incorporating nanocellulose on its properties.